PsycEXTRA Dataset 2004
DOI: 10.1037/e672832007-010
|View full text |Cite
|
Sign up to set email alerts
|

College Persistence on the Rise? Changes in 5-Year Degree Completion and Postsecondary Persistence Rates Between 1994 and 2000

Abstract: The National Center for Education Statistics (NCES) is the primary federal entity for collecting, analyzing, and reporting data related to education in the United States and other nations. It fulfills a congressional mandate to collect, collate, analyze, and report full and complete statistics on the condition of education in the United States; conduct and publish reports and specialized analyses of the meaning and significance of such statistics; assist state and local education agencies in improving their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 4 publications
1
56
0
Order By: Relevance
“…However, as reported by Horn (1998) and Horn and Berger (2004), between twenty to thirty percent of all first-time undergraduates initially enroll as part-time students. While attrition rates are higher for part-time students, there has been little research explicitly comparing the reaction functions across these two student populations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, as reported by Horn (1998) and Horn and Berger (2004), between twenty to thirty percent of all first-time undergraduates initially enroll as part-time students. While attrition rates are higher for part-time students, there has been little research explicitly comparing the reaction functions across these two student populations.…”
Section: Introductionmentioning
confidence: 98%
“…These individuals are not dropouts but stopouts. Recent work by Horn (1998), Horn and Berger (2004), Light (1996), as well as O'Toole, Stratton, and Wetzel (2003) discusses stopout behavior. Classifying temporary stopouts as long-term dropouts treats those who do continue their education, albeit in a discontinuous fashion, the same as those who permanently drop out.…”
Section: Introductionmentioning
confidence: 99%
“…Persistence rates appear to have risen between the early and mid-1990s, though there was no perceptible change in graduation rates (Horn and Berger, 2004). This finding suggests that this cohort of students may be persisting longer and attending multiple institutions on the road to the baccalaureate.…”
Section: Develop Additional Indicators Of Success For Different Typesmentioning
confidence: 91%
“…Three-fifths of students in public two-year colleges and one-quarter in fouryear colleges and universities require at least one year of remedial coursework (Adelman, 2005;Horn and Berger, 2004;U.S. Department of Education, 2004).…”
mentioning
confidence: 99%
“…Four decades of student retention research has shown that the vast majority of students who dropout of college will do so within their first-year of college (Horn, Berger, & Carroll, 2004;Tinto, 1993;Wood, 2012), but stopout and dropout occur throughout the college years.…”
Section: Statement Of the Problemmentioning
confidence: 99%